AN ANALYSIS OF CODE MIXING IN THE ENTERTAINMENT CORNER OF LOCAL NEWSPAPERS IN PEKANBARU - Hannisa Haris; jismulatif jismulatif; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This study seeks to explore the form of code mixing and lexical categories which are often exploited in the entertainment corners of local newspapers in Pekanbaru. It was conducted from January 2018 to July 2018. Qualitative reasearch and descriptive analysis method were applied in this study. The finding discovers that the forms of code mixing which had been observed in the entertainment corner are the insertion of words and hybrid. It also finds out that mostly 54.84% of English lexical categories have been code mixed into the entertainment corner of local newspapers in Pekanbaru were nouns. Therefore, the researcher confirms that there are some code mixing used by journalist into the entertainment corner of local newspaper in Pekanbaru.Keywords: Analysis, Code-Mixing, Entertainment Corner, Local Newspaper